Efforts to increase visitors of seven wonders ecotourism in Bantimurung Bulusaraung National Park through tourism package - Indah Novita Dewi; Nur Hayati (Jurnal Penelitian Kehutanan Wallacea, 2021)
Bantimurung Bulusaraung National Park (Babul NP.) has seven excellent tourist areas which are commonly called seven wonders. Each has attractions that are mostlyspecial interest tours. The distribution of visitors from seven wonders area has not been evenly distributed. Bantimurung is the most visited by tourists, while others are relatively unknown. The purpose of this research is to develop a strategy to increase the number of visitors in Babul NP. through a high-value seven wonders ecotourism package. This research was a qualitative research and conducted in March 2018 to December 2019. Data were collected through interviews, observation, and literature studies. Data analysis was carried out in stages. The condition of seven wondersecotourismwere explained by descriptive qualitative analysis. The development strategy to increase the number of visitors was arranged by qualitative descriptive analysis and identification of internal (Strength, Weakness) and external (Opportunity, Threat) factors. One of the results from identification of internal and external factors showed the development strategy could be carried out by arranging tour packages. The tour packages designed are: Family tour package consisting of Bantimurung, Leang-Leang, and Pattunuang; Educational tour package consisting of Bantimurung (Butterfly Sanctuary), Leang-Leang, Pattunuang, Karaenta; Challenging adventure tour package consisting of Pattunuang-Leang Pute; and Family tour package consisting Leang Londrong-Mountains Bulusaraung. The packages arranged based on location, tourism attraction, combination of tourism object with a lot visitors and not, and visitors segmentation. The packages can besuccessful if they collaborate with related parties, promote the right and attractive markets and media.